2019
DOI: 10.1097/acm.0000000000002836
|View full text |Cite
|
Sign up to set email alerts
|

Which Student Characteristics Are Most Important in Determining Clinical Honors in Clerkships? A Teaching Ward Attending Perspective

Abstract: WHAT DEFINES AN HONORS 3 RD YEAR MEDICAL STUDENT DURING HOSPITAL WARDS? ACGME CORE COMPETENCIES How much emphasis do you place on each of the following characteristics when designating a student as "honors" (or the highest grade)? Circle a number Patient Care (PC): Provides patient care that is compassionate, appropriate, and effective for the treatment of health problems and the promotion of health 1= less emphasis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Patient interaction, medical knowledge, and communication were significant for both genders in the multivariate analysis. The importance of these clinical domains is reflected in existing literature; in a survey of faculty, clinical reasoning and professionalism were 2 of the most influential factors when grading students . Our univariate analysis found that professionalism, resource utilization, compassion, and teamwork were all positively correlated with overall evaluation, but none of these factors were significantly associated with this outcome in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Patient interaction, medical knowledge, and communication were significant for both genders in the multivariate analysis. The importance of these clinical domains is reflected in existing literature; in a survey of faculty, clinical reasoning and professionalism were 2 of the most influential factors when grading students . Our univariate analysis found that professionalism, resource utilization, compassion, and teamwork were all positively correlated with overall evaluation, but none of these factors were significantly associated with this outcome in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 64%
“…The importance of these clinical domains is reflected in existing literature; in a survey of faculty, clinical reasoning and professionalism were 2 of the most influential factors when grading students. 20 Our univariate analysis found that professionalism, resource utilization, compassion, and teamwork were all positively correlated with overall evaluation, but none of these factors were significantly associated with this outcome in the multivariate analysis. These data suggest that, although these factors were significant and positively correlated with individual performance, overall grade was more likely associated with alternative factors in this cohort.…”
Section: Jama Network Open | Medical Educationmentioning
confidence: 68%
“…The few formal studies we found, limited exclusively to medical student education, constitute preliminary investigations [22][23][24]. Notably, displays of curiosity by medical students are associated with achieving clinical honors on clerkships [25].…”
Section: Clinical Curiositymentioning
confidence: 84%
“…Developing a better understanding of what characteristics exceptionally performing medical students possess upon entrance to medical school is necessary if we seek to optimize the recruitment of students with the best potential to be exceptional performing physicians. As a medical student, top characteristics that faculty consider when assigning an honors clerkship grade are curiosity, dependability, taking ownership, and high ethical standards (Herrera et al, 2019); while top characteristics valued in first year residents are responsibility, teamwork, empathy, and prioritization (Furstenberg and Harendza, 2017). Other research demonstrates that conscientiousness, extraversion, and grit are likely associated with successful clinical performance (Haight et al, 2012;Miller-Matero et al, 2018;Cortez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%